Improving Students’ Speaking Skill in Descriptive Text Using Mind Mapping Method at Seventh Grade Junior High School - Darussalam, Gilang Manik; Ningrum, Ary Setya Budhi (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Speaking is one of the English language skills that must be mastered by students where there are students who can express their opinions, ideas and understanding in capturing the material presented by the teacher. There are several methods used to improve students' English speaking skills, this time the researcher used the mind map method. The focus of this research is to improve students' speaking ability in English descriptive text. This method is implemented to the research subjects of class VII students of MTs Raudlatuth Thalabah Kediri. The research method uses classroom action research and the data collection starts from student observations, pre-test, and post-test. Based on the results of the findings, the researchers found that the development of students' speaking skills from each test result that had been presented with the explanation of the last post-test data as follows, the lowest score of students in the second cycle post-test was 60.00 and the highest score was 90.00 then the class average value in the second cycle post-test was 78.1481 so that this study resulted in that this mind map method succeeded in improving students' English speaking skills even though some researchers found obstacles in the research process.